PARENTING SELF-PERCEPTION: A COMPARATIVE STUDY OF TEENAGE AND EMERGING ADULT MOTHERS IN WEST JAVA: Persepsi Diri terhadap Pengasuhan: Sebuah Studi Komparatif antara Ibu Berusia Remaja dan Emerging Adult di Jawa Barat - Hildayani, Rini; Agustiani, Hendriati; Purwono, R. Urip; Noer, Afra Hafny (Jurnal Ilmu Keluarga dan Konsumen, 2024)
Some studies have shown differences in parenting practices between teenage and emerging adult mothers; however, not all research has found this to be the case. This study aims to examine differences in perceptions of parenting roles between teenage and emerging adult mothers. Perceptions of parenting roles are associated with parenting practices and encompass four dimensions: parenting competence, parenting satisfaction, parenting investment, and integration/role balance. This research is a non-experimental study using a between-subjects design. A total of 86 teenage mothers (15–19 years old) and 86 emerging adult mothers (20–23 years old) participated in the study. Parenting self-perception was measured using the Self-Perception of Parenting Role (SPPR), and the data were analyzed using a t-test. The results indicated significant differences in parenting self-perception between teenage and emerging adult mothers in the areas of parenting competence, parenting satisfaction, and integration/role balance. Emerging adult mothers demonstrated higher competence, greater satisfaction, and a better ability to integrate the various roles they undertake. In contrast, no significant differences were found between the two groups in parenting investment. These findings support Law Number 16 Year 2019, which permits marriage for men and women aged 19 years and older.